The Disordered Spindly C-terminus Interacts with RZZ Subunits ROD-1 and ZWL-1 in the Kinetochore through the Same Sites in C. Elegans. Issue 4 (19th February 2021) - Henen, Morkos A.; Myers, Walter; Schmitt, Lauren R.; Wade, Kristen J.; Born, Alexandra; Nichols, Parker J.; Vögeli, Beat
Graphical abstract: Highlights: C-terminal part of dynein adaptor Spindly binds the ROD/ZW10/ZWILCH complex at the kinetochore. C. elegans Spindly-C is disordered but comprises two regions with variable α-helical propensity. Spindly-C interacts with ROD-1 and ZWL-1 via the same two sequentially remote disordered segments. Spindly-C binding sites on ROD-1 in the ROD-1/ZWL-1 complex are abrogated by presence of ZWL-1. Abstract: Spindly is a dynein adaptor involved in chromosomal segregation during cell division. While Spindly's N-terminal domain binds to the microtubule motor dynein and its activator dynactin, the C-terminal domain (Spindly-C) binds its cargo, the ROD/ZW10/ZWILCH (RZZ) complex in the outermost layer of the kinetochore. In humans, Spindly-C binds to ROD, while in C. elegans Spindly-C binds to both Zwilch (ZWL-1) and ROD-1. Here, we employed various biophysical techniques to characterize the structure, dynamics and interaction sites of C. elegans Spindly-C. We found that despite the overall disorder, there are two regions with variable α-helical propensity. One of these regions is located in the C-terminal half and is compact; the second is sparsely populated in the N-terminal half. The interactions with both ROD-1 and ZWL-1 are mostly mediated by the same two sequentially remote disordered segments of Spindly-C, which are C-terminally adjacent to the helical regions. The findings suggest that the Spindly-C binding sites on ROD-1 in the ROD-1/ZWL-1 complex context are either shielded or conformationally weakened by the presence of ZWL-1 such that only ZWL-1 directly interacts with Spindly-C in C. elegans